Authoritarian attitudes in Russia: Right‐wing authoritarianism and social dominance orientation in the modern Russian context. Issue 4 (19th February 2022) - Grigoryev, Dmitry; Batkhina, Anastasia; Conway, Lucian Gideon; Zubrod, Alivia
Abstract : The study of authoritarianism has a long history in the field of psychology; however, much of this research focuses on Western countries, especially the United States. In effort to better understand authoritarianism cross‐culturally, we explore the current state of authoritarianism in an important cultural context: Russia. Thus, the current paper reports on large‐scale research of right‐wing authoritarianism and social dominance orientation in the modern Russian context. Six studies (total N = 1, 358) included personality traits, basic human values, social beliefs, and intergroup attitudes that allowed us to comprehensively consider authoritarian attitudes in Russia. The results showed that personological profile and pattern of reaction to threat among Russian authoritarians is similar to Western authoritarians. However, economic views inherited from Soviet ideology make Russians differ in their view of economic conservatism from that supported by Western authoritarians. These data provide insight into the psychology of authoritarianism as well as explore novel aspects of Russian culture.